Geomechanical analysis from well log for brownshale hydrocarbon development in the Bengkalis Trough, Central Sumatra Basin, Indonesia. Issue 5 (2nd November 2021) - Buntoro, Aris; Prasetyadi, C.; Wibowo, Ricky Adi; Suranto, A. M.
ABSTRACT: Geomechanical analysis using well log can be used to determine the fracable zone. Fracability is a parameter applied in the development of shale hydrocarbon to overcome the weaknesses in determining the fracable zone which was previously only based on high brittleness and considered a good hydraulic fracking candidate. The fracability model from the results of geomechanical analysis is used as the basis for hydraulic fracking planning for the development of Brownshale hydrocarbon in the Bengkalis Trough area, as a case study. Therefore, it has good development prospects. The geomechanical analysis of well BS-03, is the only well that penetrated the Brownshale formation. The geomechanical parameters investigation consists of Young's modulus, Poisson's ratio, unixial compressive strength, brittleness index, and the fracability index. Therefore, the fracability model is built by correlating the depth interval of the Brownshale formation and the geomechanical parameters, in order to determine the Brownshale formation interval as the basis for the location selection process and the hydraulic fracking interval. The results of geomechanical analysis show an interesting phenomenon in the fracability index, with negative and positive depth intervals at the top and bottom, respectively. The upper and lower depth intervals represent fracture barrier and fracable zone interval. Abbreviations vp : primary wave velocity (km/sec); vs : secondary wave velocity (km/sec); ρ: rock density (g/cc); E: Young's Modulus (MPa); υ: Poisson's ratio (dimensionless); UCS: unconfined compressive strength, MPa; Vp : primary wave velocity (km/sec) where; Ebrittleness : Young's modulus of brittleness, fraction; Emin : Minimum Young's modulus, MPa; Emax : Maximum Young's modulus, MPa; FI: Fracability index, fraction; Bn : Brittleness normalization, fraction; En : Young's Modulus normalization, fraction; B: Brittleness at analyzed depth, fraction; Bmin : Minimum brittleness in the formation was investigated, fraction; Bmax : Maximum brittleness in the formation was investigated, fraction; β: Biot's effective stress constant; Bc: Skempton's coefficient